The identity of Lepidagathis yappii (Acanthaceae) - Deng, Yunfei; Sugumaran, Manickam; Lin, Zheli (Phytotaxa, 2019)
The examination of type material of Lepidagathis yappii reveals that it is conspecific with Thysanostigma odontites. The description, distribution and conservation status are provided.